DAMPAK KEBIJAKAN MONETER TERHADAP STABILITAS RUPIAH - Azhar Bafadal (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2011)
This research aimed to study the impact of monetary policy on the rupiah stability. Variables used were the interest rate of Bank Indonesia Certificate (SBI), the rate of inflation (IHK), the exchange rate of rupiah against the US dollar (Kurs) and the money supply in the narrow sense (M1). Data used were of quarterly time series data of Bank Indonesia and Central Bureau of Statistic, covering 2002.1-2010.4. The analysis was undertaken by using a vector autoregression model (VAR), through the Impulse Response Function (IRF) and Forecast error variance decomposition (FEVD). The research results showed that in the sort run shocks of SBI decreased the inflation rate, and in the long run the inflation rate was constant. The exchange rate tended to be appreciated in the short run and long run although in a small magnitude. Money supply decreased with a minor fluctuation. Initially, the money supply shocks increased the interest rate of SBI, but decreased in the long run. The rate of inflation fluctuated in the sort run but it was constant in the long run. The exchange rate was depreciated both in the sort run and in the long run.